Verschriftungsprinzipien im geschriebenen Dialekt: WhatsApp-Nachrichten aus Südtirol - Alber, Birgit; Frey, Jennifer-Carmen; Glaznieks, Aivars; Glück, Alexander; Kokkelmans, Joachim (Linguistik Online, 2024)
Although the orthographic norm of the standard language has dominated most written registers of German, social media and other non-standardized digital contexts have recently given rise to the written use of dialects and vernaculars in informal communication. The written use of non-standard dialects is especially wide-spread in the south of the German-speaking area, e. g. in Switzerland, Bavaria, Austria and South Tyrol, where various studies have reported the use of dialectal forms in digital contexts such as Chatrooms, WhatsApp or Facebook (cf. Christen 2004; Glaznieks/Frey 2018). Using a corpus of South Tyrolean WhatsApp chats with corresponding audio recordings of the chat authors retelling the chat contents, we analyze four phonetic-phonological phenomena of Tyrolean dialects, characteristic of the southern German-speaking area: pre-consonantal s-retraction, the neutralization of the phonemes /p/ and /b/ in word-initial position, vowels undergoing umlaut or unrounding and the realisation of r in the coda of unstressed syllables. In particular, we analyze if and how these phenomena of the dialect are represented in the written form. The results show that Standard German graphematic conventions form the basis for most dialect spellings in WhatsApp chats. However, they are sometimes abandoned for the benefit of spellings that explicitly represent dialectal pronunciations. Interestingly, in some cases these dialectal spellings do not correspond to the pronunciation of the writers who, instead, opt for a pronunciation closer to that of the standard language.